A data-based review on norfloxacin degradation by persulfate-based advanced oxidation processes: Systematic evaluation and mechanisms - Pan Wang; Huixuan Zhang; Zhuohan Wu; Zhao, Xiao; Ying Sun; Na Duan; Zhidan Liu; Liu, Wen (Chinese Chemical Letters, 2023)
Persulfate-based advanced oxidation processes (AOPs) have obtained increasing attention due to the generation of sulfate radical (SO4•‒) with high reactivity for organic contaminants degradation. Numerous activation methods have been used to activate two common persulfates: peroxymonosulfate (PMS) and peroxydisulfate (PDS). However, the comparisons of activation methods and two oxidants in the comprehensive degradation performance of the target contaminant are still limited. Thus, taking norfloxacin (NOR) as the target contaminant, we proposed five key parameters (the observed pseudo-first-order rate constant, kobs; average mineralization rate, rm; utilization efficiency of catalyst, Ucat; utilization efficiency of oxidant, Uox; and net utilization efficiency of oxidant, Uox’) to quantify the comprehensive degradation performance of NOR. The irradiation affected target pollutants, catalysts, and oxidants, leading to an improved degradation performance of NOR. Various heterogeneous catalysts were compared in terms of the key elements contained. Fe, Co, and Mn-based materials performed better, while carbon-based catalysts performed poorly on NOR degradation. The overall degradation performance of NOR was different for PMS and PDS, which can be ascribed to their varied reaction pathways towards NOR, but stemmed from different properties of PMS and PDS. Besides, the effect of pH on the degradation efficiency of NOR was investigated. A neutral solution was optimal for PMS system, while an acidic solution worked better for PDS system. Finally, we analyzed the molecule structure of NOR by density functional theory (DFT) calculation to study the sites easy to attack. Then, we summarized four typical degradation pathways of NOR in SO4•‒-based AOP systems, including defluorination, piperazine ring cleavage, piperazine ring oxidation, and quinoline group transformation.
Keywords: Antibiotic degradation; Heterogeneous catalysts; Norfloxacin; Persulfate-based AOPs; Sulfate radical